PEMBUATAN EDIBLE COATING DARI PATI BIJI DURIAN SEBAGAI PELAPIS BOLU KEMOJO - Raharjo, Eko; Yusmarini, Yusmarini; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Compared to the content of other plants, durian seeds contain high starch. The high amylose and amylopectin components in durian seed starch are considered to be sufficiently pro- effective to be used as a base material in edible coating which can be consumed. The use of glycerol has a role as a plasticizer in improving the properties of good permeability as an edible layer. This study aims to know the best amount in the application of edible coating on kemojo cake. This study used a completely randomized design (RAL), consisting of 5 treatments in which each treatment performed 3 repetitions. The treatments in this study were AB0 (without immersion as control), AB1 (once immersion), AB2 (twice immersions), AB3 (thrice immersions), and AB4 (four times immersions). The results show that the pH edible coating is 5 and the viscosity is 6.07 cP. The best treatment was thrice times immersions (AB3) with water content of 35.71%, weight decreased 6.79%, and TBA 1.85 mg malonadehid / kg. Texture 3.13 (rather hard) and aroma 4.13 (rancid). Keywords: Cellulose, water hyacinth, glycerol, carrageenan.